(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Nutrition is the biochemical of physiological process by which an organism uses food to support its life. It provides organisms with nutrients, which can be metabolized to create energy & chemical structures. Failure to obtain sufficient nutrients causes malnutrition, Nutritional science is the study of nutrition, through it typically emphasizes human nutrition.